Why do parents use packaged infant foods when starting complementary feeding? Findings from phase one of a longitudinal qualitative study - Anna Isaacs; Kimberley Neve; Corinna Hawkes (BMC, 2022)
Abstract Background The first 1000 days in a child's life, from conception to age two, are a critical period for establishing a child's health and development. One important element is the diet that children receive during this time. Dietary intake of infants in the UK has been shown to be high in sugar and salt, with overall energy intakes exceeding recommendations by the time they are two years of age. Commercial infant food, which forms approximately 40-60% of infants' dietary intake, was identified in 2011 as the main contributor to sugar intake for infants aged 4-9 months in the United Kingdom. Further, evidence demonstrates inconsistencies between national recommendations on infant feeding and some of these products in terms of the type available, their nutritional value and product labelling and marketing. Given their role in infants' diets, it is important to understand parental perceptions of these products and why they are chosen. Methods The study comprised the first phase of an in-depth, longitudinal qualitative study which explored parents' experiences of introducing solid foods to their infants over the first year of feeding. 62 parents/ carers were recruited to this phase when their infants were four-six months old. Data collection involved semi-structured interviews and a photo-elicitation exercise. Data from interview transcripts which focused on the purchase and use of packaged purees and commercial snacks were analysed thematically. Results Parents/ carers drew on a range of reasons for buying both packaged purees and commercial snacks for their infants. These included anxiety over food preparation, food safety, convenience, cost effectiveness, the pull of brand eco-systems for packaged purees, and the way in which commercial snacks provide opportunities for safe development of motor skills, keep infants occupied, and allow them to take part in family rituals. Conclusion In considering the use of packaged products as a food source for infants in public health nutrition policy, it is important to understand the broad range of factors that shape parents decisions ranging from the way that products are advertised and perceived, to the non-nutritive roles that they play.